SINCE ANCIENT PERSIAN GARDENS TO MODERN VERTICAL GARDENS AND ROOF GARDENS - Mohammad Baharvand (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Iran is a plateau surrounded by mountains, and with the exception of some rivers in the north and south, it is a relatively bare country. In this situation, creating manmade gardens and green lands need not only scientific information about water management and land properties but also need a professional aesthetic view. Persian gardens that are created in this severe climate are some of the most beautiful and thoughtful manmade structuresin the world. Although the structures influence other countries by different climatic conditions, the structureshave remained stablefor centuries.In this study, the attempt is made to understand what the gardensare and why humans try to create gardens. The question is how Persian gardens were formed in the beginning and how theirstructures have persistedover time in different climates and different topography.Currently, due to the busy modern lifestyle and land limitations, the connection between human and gardens is fractured.Therefore, some ideas, such as applying vertical gardens and roof gardens, are described as a replacement to increase the connection between humans and greenery.